THE CORRELATION BETWEEN READING INTEREST AND READING COMPREHENSION OF JUNIOR HIGH SCHOOL STUDENTS IN PEDAMARAN - Nabila Febiola; Annisa Astrid; Deta Desvitasari (Wiralodra English Journal, 2026)
The aim of this study was to examine the relationship between reading interest and reading comprehension of ninth-grade pupils. Students from two junior high schools participated in the study, which employed a correlational approach. A reading test and a questionnaire on reading interest were used to gather data. The Pearson Product-Moment Correlation was used to analyze the relationship between the two variables. The findings revealed a substantial correlation between reading interest and reading comprehension, with a p-value of 0.001 (<0.05). A somewhat positive correlation was indicated by the Pearson correlation coefficient of 0.519. Additionally, a regression test with a p-value of less than 0.001 verified a significant positive relationship. The results showed that students' enthusiasm in reading had a beneficial impact on their comprehension of texts, as it explained 26.9% of the variance in reading comprehension. Fostering reading interest may enhance comprehension abilities, according to this study, which offers insightful information about the relationship between reading interest and understanding. Other approaches to collect more accurate data and expand on these findings should be investigated in future studies.